A review on the treatment of hyperlipidemia with Erchen Decoction - Tian, Xinyang; Liu, Peiyu; Wang, Ruolin; Hou, Yawei; Zhou, Ying; Wang, Chunyan; Zhang, Guiju (Frontiers in Pharmacology, 2024)
Hyperlipidemia, commonly referred to as dyslipidemia, is characterized by elevated serum cholesterol and/or triglyceride levels. This condition contributes significantly to the high mortality rates associated with cardiovascular diseases, posing a serious threat to global health. Although statins remain the predominant pharmacological treatment for hyperlipidemia, their associated side effects have led to a growing interest in alternative therapeutic approaches. Traditional Chinese Medicine (TCM) is exploring these alternatives, with the Erchen Decoction (ECD) emerging as a promising candidate. This review aims to summarize current clinical research, elucidate the mechanisms of action, and assess the compatibility of ECD in the management of hyperlipidemia. By doing so, we hope to provide valuable insights and references for clinical practice and future research. 1 Introduction Hyperlipidemia usually refers to elevated levels of total cholesterol (TC), triglycerides (TG), and/or low-density lipoprotein cholesterol (LDL-C) in the serum (Li et al., 2023a), along with a decrease in high-density lipoprotein cholesterol (HDL-C) (Luo et al., 2020). An abnormality in any of these indicators can be diagnosed as hyperlipidemia, also known as dyslipidemia. The prevalence of